Peran Pemimpin dalam Pengelolaan Perubahan dan Pengembangan Organisasi: Studi Kasus Pembinaan Guru Baru di SLH Sangihe - Alfian Angi; Nelli Tambunan; Rita Kristina; Sherine Gracia Yudhi; Widuri Gito Rumjati (Magister Teknologi Pendidikan Fakultas Pascasarjana Pendidikan Universitas Pelita Harapan, 2025)
Education plays a crucial role in shaping individuals, and the success of a school organization is greatly inlfuenced by the roles of both leaders and teachers, particulary first-year teachers. At Sekolah Lentera Harapan Sangihe, first-year teachers face various challanges in adapting professionally and culturally. To address this, the school principal has taken strategic steps through induction and mentoring programs, aligned with the Change Pyramid concept, to support the effective transformation of new teacher roles. The study was designed to analyze the critical role of a leader in managing change and developing an organization, with an emphasis on a case study at SLH Sangihe that highlighted the difficulties in mentoring new teachers. The changes encompass various aspects, including adapting to educational developments, enhancing teaching quality, and meeting the needs of new teachers. The research method employed is qualitative, with a case study as the primary method. The research results indicate that SLH Sangihe is currently undergoing changes at the level of change tasks and change roles. The leader of SLH Sangihe opts for incremental change options on gradual improvements. As a result following the research, the implementation of educational strategies is deemed effective in managing internal changes as it aims to transform the values and beliefs of individuals, supporting the desired changes and committing to the organizational values.